2019
DOI: 10.1002/mgg3.605
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in 51 early onset non‐familial CRC cases

Abstract: Background Colorectal cancer ( CRC ) cases with an age of onset <40 years suggests a germline genetic cause. In total, 51 simplex cases were included to test the hypothesis of CRC as a mendelian trait caused by either heterozygous autosomal dominant or bi‐allelic autosomal recessive pathogenic variants. Methods The cohort was whole exome sequenced ( WES ) at 100× coverage. Both a dominant‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…It is notable that all the women in our series lacked any known predisposition to CRC, including IBD, alcohol consumption, hereditary CRC syndromes and a family history of CRC (26, 27, 28, 29, 30, 31, 32). No germline mutations were detected, which is consistent with a study that found low probability of having a known germline mutation in patients with CRC <40 years old (33). However, numerous VUS were identified in all of the women, which may merit further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…It is notable that all the women in our series lacked any known predisposition to CRC, including IBD, alcohol consumption, hereditary CRC syndromes and a family history of CRC (26, 27, 28, 29, 30, 31, 32). No germline mutations were detected, which is consistent with a study that found low probability of having a known germline mutation in patients with CRC <40 years old (33). However, numerous VUS were identified in all of the women, which may merit further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…DIDO1 was recently shown to recognize the histone 3 lysine residue 4 trimethylation mark in a pH-dependent manner through a PHD domain ( Tencer et al. , 2017 ) and was identified as a possible germline variant in familial colorectal cancer ( Thutkawkorapin et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypes that were studied included either polyposis, familial colon and/or rectal cancer, or a mixture of the aforementioned phenotypes. Age-based inclusion criteria were applied in twelve out of the 32 unique discovery cohorts [ 13 , 43 , 47 , 49 , 53 , 54 , 56 , 59 , 64 , 65 , 67 , 69 , 70 , 71 , 72 , 75 , 76 ]. However, this age-based inclusion criterion was heterogeneous ranging from an age at diagnosis ≤35 years [ 47 ] to diagnosis <60 years [ 43 ], to at least one relative diagnosed <60 years [ 53 , 64 , 69 , 72 , 75 , 76 ].…”
Section: Strategies For Identification Of Rare High-penetrant Riskmentioning
confidence: 99%
“…In general, we observed prioritization based on either complete screening of WES or WGS data or, more targeted, by focusing on specific genes or regions that are more likely to be involved in hereditary cancer. The main applied variant prioritization strategies included linkage ( n = 8 studies [ 41 , 43 , 52 , 55 , 61 , 66 , 73 , 75 ]), variants shared among affected relatives or absence of the variant in unaffected relatives ( n = 19 studies [ 41 , 43 , 48 , 51 , 52 , 53 , 55 , 57 , 60 , 61 , 63 , 64 , 66 , 67 , 68 , 69 , 70 , 74 , 76 ]) and gene function ( n = 14 studies [ 13 , 47 , 53 , 57 , 58 , 59 , 63 , 64 , 65 , 71 , 72 , 74 , 75 , 76 ]). Other approaches include the prioritization of recurrent variants ( n = 7 studies [ 13 , 39 , 40 , 44 , 50 , 56 , 65 ]) and prioritization based on expected recessive or dominant mode-of-inheritance ( ...…”
Section: Strategies For Identification Of Rare High-penetrant Riskmentioning
confidence: 99%
See 1 more Smart Citation